Text, for the Record: An ELFK Pastor vs a Nazi Creed - Brandt, Samuel (Lutheran quarterly, 2021)
This article presents an excerpt from Wider das neue Heidentum, the Evangelisch-Lutherische Freikirche's response to Nazi ideology found in Der Mythus des 20. Jahrhunderts and Wilhelm Schwaner's Germanen-Bibel. Its sophisticated and confident formulation stands out against the ambivalence of its age and its insights into the nature of National Socialism can be considered prophetic. The unmistakable juxtaposition of orthodox Lutheranism and National Socialism come into vivid focus.